Tips for avoiding ethical problems in scientific publication (2014)
The Committee on Publication Ethics (COPE) —conformed by the main scientific publishers— has warned about the increasing number of ethical problems in scientific publication and recent scandals seem to indicate that ethical misconduct is repetitive. Ethical problems in scientific publication arise when the person deviates from expected moral behavior. Misconduct may be explained, at least in part, because many postgraduate students and young researchers seem to understand that ethical problems are only related to plagiarism of complete works or duplication of publications, and because it seems to be a lack of knowledge of the ethical standards in scientific publication. However, there are many other aspects conducing to ethical problems. The objective of this paper is to discuss and spread the ethical position of the main scientific publishers and researchers with the aim of build a unified point of view. In this paper, seventeen tips for avoiding ethical problems in scientific publication are presented, explained and discussed. I hope that this work will be valuable for postgraduate students and young researchers and answers many common questions about ethics in scientific publication.